Adoption and Utilization of Cloud Computing in Academic Libraries - Adio, Emmanuel O.; Ozoh, Uchenna L.; Bakari, Sadiku U. (POMLIF Journal of Library and Information Science, 2021)
The development in information technology has changed the way by which libraries disseminate information to their patrons. Cloud computing in libraries deal with how libraries are able to carry out their activities in digital format especially in academic libraries. The paper therefore discussed the meaning of cloud computing, its concept and also the importance of cloud computing, types of cloud computing models available to libraries for storage of large date and its implications into various library services and operations.